2008
DOI: 10.1369/jhc.2008.950287
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Decorin by Human Malignant and Benign Vascular Tumors

Abstract: An increasing amount of evidence indicates that a small extracellular chondroitin/dermatan sulfate proteoglycan, decorin, is indirectly involved in angiogenesis. Given that angiogenesis is a sine qua non for tumor growth and progression, we attempted to examine whether human malignant vascular tumors differ from human benign vascular tumors in terms of their decorin expression and synthesis. CD31 immunostaining demonstrated that the human malignant vascular tumors Kaposi's sarcoma and angiosarcoma were filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 38 publications
(40 reference statements)
4
43
0
Order By: Relevance
“…The results demonstrated that immunoreactivity of decorin was clearly detectable in the connective tissue stroma within tumor nests. This finding is compatible with the previous study that demonstrated negative and positive expressions in Kaposi's sarcoma and benign hemangioma, respectively [4]. Localization of decorin staining is supposed to be similar to collagen I.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results demonstrated that immunoreactivity of decorin was clearly detectable in the connective tissue stroma within tumor nests. This finding is compatible with the previous study that demonstrated negative and positive expressions in Kaposi's sarcoma and benign hemangioma, respectively [4]. Localization of decorin staining is supposed to be similar to collagen I.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, decorin has been shown to regulate endothelial cell-matrix interactions during angiogenesis [5]. Furthermore, a current publication on benign and malignant vascular tumors demonstrated that expression patterns of decorin were differed from malignant to benign vascular tumors [4]. They showed that there was no detectable decorin immunoreactivity within the tumor mass in the Kaposi's sarcoma or angiosarcoma group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is further substantiated by a recent report where the expression of decorin was evaluated as a function of tumor malignancy. Sarcomas exhibited almost a complete absence of decorin in contrast to hemangiomas, where decorin was predominantly detected in the surrounding stroma (74). Aside from the potent pro-migratory, pro-invasive, and pro-survival roles inherent with aberrant Met activation (75), the Met signaling axis is powerfully pro-angiogenic, specifically promoting VEGFA-mediated angiogenesis (76,77).…”
mentioning
confidence: 99%